Pentingnya Penerimaan Diri Bagi Remaja Panti Asuhan Islam - Kuncoro Lestari Anugrahwati; Anak Agung Ketut Sri Wiraswati (Universitas Islam Indonesia, 2020)
ABSTRACTThe adolescents in orphanage have different way of feeling loved by their parents’ figure. This divergent with adolescents in general might raise various problems for developing their identities. They get the stigmas from society as “orphan”, and it becomes hindrance in their development. Thus, to boost their own development, self-acceptance is one factor to be concerned. The purpose of this training is to help adolescents to achieve self-acceptance. This research is conducted with experimental method based on Bastaman’s factor of self-acceptance. Participants were given training related to self-insight, meaning of life, changing attitude, self-commitment, directed activities, and social support to increase the self-acceptance of adolescents in orphanage X. Conducted evaluations showed the significancy of 0,014 on t-test between pretest and post-test. This shows the impact of the training on adolescents in the orphanage to develop their self-acceptance for their well- being.ABSTRAK Tidak semua remaja memiliki keberuntungan dalam hal memperoleh dukungan sosial dan kasih sayang dari orangtuanya. Hal ini menimbulkan berbagai problematika bagi remaja dalam mengembangkan identitasnya. Label sebagai anak didik panti asuhan atau yatim piatu menjadi sumber stres bagi remaja, sebab menghasilkan berbagai kemungkinan pengalaman buruk pada anak didik panti asuhan di masa depan. Sasaran dari pelatihan ini adalah membantu remaja di panti asuhan agar mampu mencapai penerimaan diri. Penelitian ini dilakukan dengan metode eksperimen berdasarkan faktor penerimaan diri dari Bastaman. Partisipan diberikan pelatihan yang memuat self-insight, meaning of life, changing attitude, self-commitment, directed activities, dan social support untuk meningkatkan penerimaan diri remaja panti asuhan. Perbandingan tes awal dan tes akhir menunjukkan adanya perbedaan penerimaan diri dengan nilai signifikansi 0.014. Artinya, pelatihan ini dapat meningkatkan penerimaan diri pada remaja Panti Asuhan Islam.